2016
DOI: 10.1037/bul0000046
|View full text |Cite
|
Sign up to set email alerts
|

What limits working memory capacity?

Abstract: We review the evidence for the three principal theoretical contenders that vie to explain why and how working memory capacity is limited. We examine the possibility that capacity limitations arise from temporal decay; we examine whether they might reflect a limitation in cognitive resources; and we ask whether capacity might be limited because of mutual interference of representations in working memory. We evaluate each hypothesis against a common set of findings reflecting the capacity limit: The set-size eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
213
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(232 citation statements)
references
References 291 publications
2
213
2
2
Order By: Relevance
“…Our data show significant individual differences in performance, which has been a hallmark of the literature to date and has proven useful in the theoretical analysis of capacity limitations in working memory [25], though it is often obscured through the presentation of group data. When we examine the individual-subject results, we progressively reduce the differences in performance between subjects through our experimental progression by calibrating to individual baseline performance (1a-1b) and removing stimulus-based confounds in the experimental paradigm (1b-2).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our data show significant individual differences in performance, which has been a hallmark of the literature to date and has proven useful in the theoretical analysis of capacity limitations in working memory [25], though it is often obscured through the presentation of group data. When we examine the individual-subject results, we progressively reduce the differences in performance between subjects through our experimental progression by calibrating to individual baseline performance (1a-1b) and removing stimulus-based confounds in the experimental paradigm (1b-2).…”
Section: Discussionmentioning
confidence: 85%
“…That is not to say that these alternative theories do not have a role in our overall understanding of the processes of memory, nor that they do not influence one another in their respective theoretical progression, as they clearly do [2]. It is also the case that more general theories of attention and integration of information must be involved to provide a full account of the underlying processes [3538], and understanding the complex nature of working memory in all its forms remains an ongoing challenge [25]. In light of this, and for the purpose of the current discussion of what is primarily an empirical paper, we will focus on the M-WM [1, 2, 26, 27] as has the majority of the immediately relevant literature [47].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that it is not the absolute amount of processed information that limits WM capacity, but it is rather the number of chunks into which this information can be compressed and organized (Miller, 1956;Simon, 1974; for recent reviews, see Cowan, 2001;or Gobet et al, 2001). Researchers may disagree about the specific number of units that constitute the limit of WM capacity (Cowan, 2001;Gobet & Clarkson, 2004;Luck & Vogel, 1997;Miller, 1956) or about the mechanism responsible (Cowan, 2001;Gobet et al, 2001;Oberauer et al, 2016); however, most theories of WM treat chunks as all or nothing. Current verbal learning theories do not see chunks as varying in strength, and, as a consequence, they do not consider that variation in chunk strength would affect WM capacity 11 .…”
Section: Existing Challenges For a Theory Of Frequency Effectsmentioning
confidence: 99%
“…Multinomial modeling has revealed that WM capacity correlates with encoding success, rather than with retrieval probability (Marevich et al, 2017). This correlation is one of the key puzzles that a theory of WM must explain, and Oberauer et al (2016) noted that no current resource-based account of WM can do so. The theory presented in this paper provides a natural account of for this observation -the creation and binding of novel episode nodes depletes a limited resource, and the strength or the probability of forming these nodes depends on the quantity of WM resources available.…”
Section: Better Ltm For People With More Wm Capacitymentioning
confidence: 99%
See 1 more Smart Citation